A mixed halide pure red light perovskite light-emitting diode and a preparation method thereof

CN123035852APending Publication Date: 2026-11-03LIAOCHENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611350345.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing mixed halide perovskite light-emitting diodes suffer from nonradiative recombination and ion migration problems during fabrication, resulting in low luminous efficiency and poor stability. Existing additives have failed to effectively eliminate morphological and structural defects, and the system is sensitive to the proportion of halogen components, with severe phase separation.

Method used

Zinc acetate was introduced as an additive into a CsI:PbI2:PbBr2 mixed halide perovskite precursor solution. Through the dual-site synergistic passivation effect of Zn2+ and CH3COO-, the crystallization kinetics were regulated, the film morphology was optimized, and defects were passivated, thus preparing zinc acetate modified perovskite films.

Benefits of technology

It significantly improves the photoelectric performance and operational stability of light-emitting diodes, increasing the maximum external quantum efficiency from 2.46% to 16.8%, the photoluminescence quantum yield from 10.5% to 81.2%, the carrier lifetime from 2.98 ns to 20.80 ns, reducing the nonradiative recombination rate by two orders of magnitude, and greatly improving surface uniformity and spectral stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123035852A_ABST
    Figure CN123035852A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of optoelectronic device preparation, and discloses a mixed halogen pure red light perovskite light-emitting diode and a preparation method thereof.CsI, PbI2, PbBr2 and Zn(CH3COO)2 are dissolved in a solvent according to a molar ratio of 1.5:0.8:0.2:x (0.1 < x < 2) to obtain a perovskite precursor solution modified by zinc acetate, the solution is deposited on an anode substrate, and after annealing, a perovskite light-emitting layer thin film modified by zinc acetate is obtained; a hole transport layer and an electrode are sequentially deposited on the thin film to obtain the mixed halogen pure red light perovskite light-emitting diode.By introducing zinc acetate as a multifunctional additive, the application utilizes the double-site synergistic passivation effect of Zn 2+ and CH3COO ‑ to simultaneously realize the crystallization kinetics regulation, film morphology optimization and defect state overall passivation of the mixed halogen perovskite thin film, so as to improve the photoelectric performance, spectral stability and operation stability of the light-emitting diode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of optoelectronic device fabrication technology, specifically relating to a mixed halogen pure red perovskite light-emitting diode and its fabrication method. Background Technology

[0002] In the display field, high resolution and wide color gamut technologies have become core development trends. According to the Rec. 2020 Ultra High Definition Display Color Standard, the luminescent materials used in display devices must possess extremely narrow emission spectra and precise color coordinates. Metal halide perovskites, due to their tunable bandgap, extremely narrow emission linewidth, and excellent solution processing properties, are considered an ideal choice for next-generation luminescent materials. Among them, mixed halide perovskites show great promise for pure red light-emitting diodes.

[0003] However, in the fabrication of mixed halide perovskite light-emitting diodes (LEDs), the nonradiative recombination and ion migration problems prevalent within the mixed halide perovskite films formed by solution processing severely restrict the luminous efficiency and spectral stability of the LEDs. Currently, to address these nonradiative recombination and ion migration issues in mixed halide perovskite films, researchers mainly employ ionic liquid additive methods and metal acetate additive methods to fabricate LEDs. Among these, the ionic liquid additive method utilizes ionic liquids to passivate the undercoordinated Pb in mixed halide pure red perovskite LEDs (PeLEDs). 2+ Despite the limitations, an external quantum efficiency (EQE) of 13.52% was achieved. This method primarily utilizes the interaction between cations and Pb. 2+ The coordination effect of Cs reduces defects. The metal acetate additive method uses ultra-small cesium acetate as a buried interface additive, achieving dual passivation of the interface and bulk phase, setting a 24.2% EQE record at 639 nm. This method utilizes in-situ Cs... + CsPbBr3 nanocrystals were doped with cations to improve the photoluminescence quantum yield (PLQY) and device efficiency.

[0004] Despite the progress made in the aforementioned research, the following shortcomings remain: Existing preparation methods primarily use additives targeting single types of defects, failing to simultaneously and effectively eliminate both morphological defects (such as grain disorder and pinholes) and structural defects (such as halogen vacancies and undercoordinated ions) prevalent in mixed halide perovskite films. This results in unresolved issues of nonradiative recombination and ion migration. Furthermore, existing mixed halide perovskite systems emitting pure red light near 683 nm are highly sensitive to the halogen component ratio, leading to significant phase separation and ion migration problems. In addition, existing mixed halide pure red PeLEDs generally exhibit low EQE and poor operational stability (T0). 50 Their lifespan is typically only a few minutes, which is far from meeting the needs of practical applications. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a mixed halogen pure red perovskite light-emitting diode and its fabrication method. This invention introduces zinc acetate as an additive into a CsI:PbI2:PbBr2 mixed halogen perovskite precursor solution, utilizing its Zn... 2+ and CH3COO - The dual-site synergistic passivation effect simultaneously achieves the crystallization kinetics regulation, film morphology optimization, and comprehensive passivation of defect states in mixed halide perovskite films, thereby improving the photoelectric performance, spectral stability, and operational stability of light-emitting diodes.

[0006] One objective of this invention is to provide a method for preparing a mixed halogen pure red perovskite light-emitting diode, comprising the following steps: CsI, PbI2, PbBr2 and Zn(CH3COO)2 were dissolved in a solvent in a molar ratio of 1.5:0.8:0.2:x to obtain a zinc acetate modified perovskite precursor solution. A zinc acetate-modified perovskite precursor solution was deposited on an anode substrate with an electron transport layer and an interface modification layer under a nitrogen atmosphere, and then annealed to obtain a zinc acetate-modified perovskite thin film light-emitting layer. A hole transport layer, a hole injection layer, and a cathode layer were sequentially deposited on a zinc acetate-modified perovskite thin film to obtain a mixed halogen pure red perovskite light-emitting diode; wherein, 0.1 <x<2。

[0007] After modification with zinc acetate, the root mean square roughness (Rm) of the zinc acetate-modified perovskite thin film luminescent layer of the present invention is [insert value here]. q The surface uniformity is 1.71 nm, which is significantly improved compared to perovskite films without zinc acetate modification.

[0008] Furthermore, the zinc acetate-modified perovskite thin film light-emitting layer is deposited by spin coating, wherein the spin coating speed is 3000 rpm to 6000 rpm, preferably 4500 rpm, and the spin coating time is 30 s to 60 s, preferably 45 s.

[0009] Furthermore, the annealing temperature is 80℃~120℃, preferably 100℃, and the annealing time is 10min~30min, preferably 20min.

[0010] Furthermore, the solvent is N,N-dimethylformamide (DMF).

[0011] Furthermore, the electron transport layer is prepared by the following method: a nano zinc oxide solution is spin-coated onto a cleaned ITO glass substrate at a speed of 3000 rpm to 5000 rpm for 45 s in an air atmosphere, and then annealed at 80°C for 30 min to obtain the electron transport layer.

[0012] Furthermore, the interface modification layer is prepared by the following method: polyethoxyethyleneimine (PEIE) is spin-coated onto the electron transport layer at a speed of 4000 rpm to 6000 rpm for 50 s in an air atmosphere, and then annealed at 100°C for 10 min to obtain the interface modification layer.

[0013] Furthermore, the hole transport layer is prepared by the following method: a poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine) (TFB) solution is deposited on a zinc acetate-modified perovskite thin film light-emitting layer by spin coating under a nitrogen atmosphere to obtain the hole transport layer; the spin coating speed is 1000 rpm to 3000 rpm, preferably 2000 rpm, and the spin coating time is 50 s.

[0014] Furthermore, the hole injection layer and the cathode layer are deposited using vacuum thermal evaporation, with a vacuum degree of 1×10⁻⁶. -4 Pa, with an evaporation rate of 0.1 nm / s to 0.3 nm / s.

[0015] The second objective of this invention is to provide a mixed halogen pure red perovskite light-emitting diode, wherein the light-emitting diode is prepared by the above-described method, comprising an anode substrate and an anode layer, an electron transport layer, an interface modification layer, a mixed halogen perovskite light-emitting layer, a hole transport layer, a hole injection layer, and a cathode layer sequentially prepared on the anode substrate.

[0016] Furthermore, the anode substrate is made of indium tin oxide (ITO) and has a thickness of 120 nm to 150 nm.

[0017] Furthermore, the electron transport layer is made of ZnO and has a thickness of 20nm~50nm.

[0018] Furthermore, the material of the interface modification layer is polyethoxyethyleneimine (PEIE), and the thickness is 5nm~15nm.

[0019] Furthermore, the material of the mixed halide perovskite luminescent layer is prepared by the above method, and the thickness is 30nm~50nm.

[0020] Furthermore, the hole transport layer is made of poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine) (TFB) with a thickness of 20 nm to 50 nm.

[0021] Further, the material of the hole injection layer is MoO₃, with a thickness of 2 nm to 5 nm.

[0022] Further, the material of the cathode layer is Ag, with a thickness of 60 nm to 80 nm.

[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) In the present invention, CsI, PbI₂, PbBr₂ and Zn(CH₃COO)₂ are co-dissolved in a solvent at a molar ratio of 1.5:0.8:0.2:x (0.1<x<2.0) to prepare a precursor solution. By setting the molar ratio of PbI₂ to PbBr₂ to 0.8:0.2, the halogen components required for 683 nm pure red light emission are locked at the source, avoiding emission peak shift caused by component deviation; subsequently, the precursor solution is deposited on a substrate and subjected to annealing treatment to obtain a zinc acetate-modified perovskite light-emitting layer thin film. In this process, acetate ions (CH₃COO - ) increase the activation energy barrier of perovskite phase transition through strong coordination with undercoordinated Pb²⁺, slowing down the nucleation and growth rates. At the same time, Zn²⁺ and its coordination groups coat the surface of crystal nuclei, and restrict the epitaxial growth of the PbX₆ 4- octahedral network through steric hindrance. The two act synergistically to inhibit excessive grain growth, thereby directly solving the problems of grain disorder and pinhole morphology defects caused by rapid crystallization in the prior art, and reducing the root mean square roughness of the zinc acetate-modified perovskite light-emitting layer thin film from 3.88 nm to 1.71 nm; on this basis, Zn 2+ as a Lewis acid anchors halogen ions (Br - / I - [[ID=]]), inhibiting halogen ion migration and halogen vacancy formation, while CH₃COO - as a Lewis base provides an electron pair to the undercoordinated Pb 2+ center to form a coordination bond, converting high-energy defect states into coordination-saturated stable states. The two act synergistically to achieve comprehensive passivation of cation and anion sites, fundamentally solving the defect in the prior art where additives only target a single type of defect and non-radiative recombination is severe, reducing the non-radiative recombination rate by two orders of magnitude (K r / K nr increases from 0.12 to 29.96), and the photoluminescence quantum yield is greatly increased from 10.5% to 81.2%; at the same time, due to the strong anchoring effect of Zn 2+ on halogen ions and the effect of acetate on Pb 2+With stable coordination, the migration of ions of each component in the mixed halide perovskite is significantly suppressed, and the phase separation problem is effectively curbed. This makes the electroluminescence peak of the light-emitting diode stable at 683nm without drift in a wide voltage range of 3~7V, solving the problem of the high sensitivity of mixed halide systems to component ratio and prominent phase separation in the prior art. Based on the above-mentioned thin film quality improvement and non-radiative recombination suppression, the maximum external quantum efficiency of the light-emitting diode is finally increased from 2.46% to 16.8%.

[0024] (2) The additive zinc acetate used in this invention is inexpensive and readily available. It can be directly added to the precursor solution without any additional process steps. It is fully compatible with existing solution processing technology and is suitable for large-scale production. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of the structure of the mixed halogen pure red perovskite light-emitting diode obtained in Example 1 of the present invention; Figure 2 The electroluminescence spectrum of the mixed halogen pure red perovskite light-emitting diode obtained in Example 1 of the present invention is shown. Figure 3 The figures show the EQE-J curve and JVL curve of the mixed halogen pure red perovskite light-emitting diode obtained in Example 1 of the present invention, wherein (a) is the EQE-J curve and (b) is the JVL curve. Figure 4 The photoelectric characteristic curves of the mixed halogen pure red perovskite light-emitting diodes obtained in Example 1 and Comparative Example 1 of this invention are shown. Figure 5 The PLQY and TRPL diagrams of the mixed halogen pure red light perovskite thin films obtained in Example 1 and Comparative Example 1 of this invention are shown, wherein (a) is the PLQY diagram and (b) is the TRPL diagram. Figure 6 The images show the morphology of the perovskite films obtained in Example 1 and Comparative Example 1, where (a) and (c) are scanning electron microscope images of the perovskite films obtained in Comparative Example 1 and Example 1, respectively; and (b) and (d) are atomic force microscope height images of the perovskite films obtained in Comparative Example 1 and Example 1, respectively. Figure 7 This is a schematic diagram illustrating the mechanism by which zinc acetate-modified perovskite achieves defect passivation and halogen anchoring in this invention. Detailed Implementation

[0026] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings.

[0027] Unless otherwise specified, all reagents used in this invention are commercially available, and all methods used are conventional techniques in the art.

[0028] Example 1 A method for fabricating a mixed halogen pure red perovskite light-emitting diode includes the following steps: (1) CsI, PbI2, PbBr2 and Zn(CH3COO)2 were dissolved in N,N-dimethylformamide in a molar ratio of 1.5:0.8:0.2:1.5 to obtain a zinc acetate modified perovskite precursor solution; (2) The nano zinc oxide solution was spin-coated at 4000 rpm for 45 s in air atmosphere and deposited onto the cleaned ITO glass substrate (i.e., the anode layer with a thickness of 120 nm). After annealing at 80 °C for 30 min, an electron transport layer with a thickness of 30 nm was obtained. (3) PEIE was spin-coated onto the electron transport layer at 5000 rpm for 50 s in air atmosphere, and then annealed at 100℃ for 10 min to obtain an interface modification layer with a thickness of 5 nm. (4) The zinc acetate modified perovskite precursor solution was spin-coated at 5000 rpm for 50s under a nitrogen atmosphere onto an ITO glass substrate with an electron transport layer and an interface modification layer. After annealing at 100℃ for 20min, a zinc acetate modified perovskite thin film light-emitting layer with a thickness of 40nm was obtained. (5) Under a nitrogen atmosphere, TFB solution was spin-coated at 2000 rpm for 50 s and deposited on the zinc acetate modified perovskite thin film light-emitting layer to obtain a hole transport layer with a thickness of 30 nm. (6) Molybdenum trioxide and silver electrodes were deposited sequentially by vacuum thermal evaporation, with a vacuum degree of 1×10⁻⁶. -4 A mixed halogen pure red perovskite light-emitting diode was obtained by vacuum thermal evaporation at a rate of 0.1 nm / s. The hole injection layer MoO3 had a thickness of 2.5 nm, and the cathode layer Ag had a thickness of 70 nm. A schematic diagram of the resulting mixed halogen pure red perovskite light-emitting diode is shown below. Figure 1 As shown.

[0029] Example 2 The only difference between the preparation method of a mixed halogen pure red perovskite light-emitting diode and Example 1 is that the molar ratio of CsI, PbI2, PbBr2 and Zn(CH3COO)2 in step (1) is 1.5:0.8:0.2:1.2.

[0030] Comparative Example 1 The only difference between the preparation method of a mixed halogen pure red perovskite light-emitting diode and Example 1 is that zinc acetate is not added in step (1).

[0031] Performance testing Figure 2 This is the electroluminescence spectrum of the mixed halogen pure red perovskite light-emitting diode obtained in Example 1. Figure 2 As can be seen, in Example 1, the electron emission intensity of the zinc acetate-modified mixed halogen pure red perovskite light-emitting diode gradually increases with the increase of the applied voltage, but the peak value of the emission peak does not change and remains at 683nm, exhibiting good spectral color stability.

[0032] Figure 3 The figures show the EQE-J curves and JVL curves of the mixed halogen pure red perovskite light-emitting diodes obtained in Embodiment 1 and the comparative example of the present invention, where (a) is the EQE-J curve and (b) is the JVL curve. Figure 3 As can be seen from (a) and (b) in Example 1, the maximum external quantum efficiency (EQE) of the zinc acetate-modified mixed halogen pure red perovskite light-emitting diode is 16.80%, and the maximum luminance is 5672 cd / m². 2 In Comparative Example 1, the maximum EQE of the unmodified mixed halogen pure red perovskite LED was 2.46%, and the maximum luminance was 2867 cd / m². 2 .

[0033] Figure 4 The graphs show the photoelectric characteristics of the mixed halogen pure red perovskite light-emitting diodes obtained in Example 1 and Comparative Example 1 of this invention. Figure 4 It can be seen that the T of the unmodified zinc acetate mixed halogen pure red perovskite light-emitting diode in Comparative Example 1 is significantly higher. 50 The time was only 4 minutes, but the T of the zinc acetate-modified mixed halogen pure red perovskite light-emitting diode in Example 1 was much shorter. 50 Increase to 180 minutes.

[0034] Figure 5 The PLQY and TRPL images of the mixed halogen pure red perovskite thin films obtained in Example 1 and Comparative Example 1 of this invention are shown, where (a) is the PLQY image and (b) is the TRPL image. Figure 5 As can be seen in (a) of Example 1, the photoluminescence quantum yield (PLQY) of the unmodified mixed halogen pure red perovskite film is only 10.5%, while the PLQY of the zinc acetate-modified mixed halogen pure red perovskite film in Example 1 increases to 81.2%. The time-resolved photoluminescence spectra (TRPL) of the perovskite films without and with zinc acetate are shown below. Figure 5As shown in (b) of the figure, the fluorescence lifetimes of the two perovskite films can be obtained from this figure. The fluorescence lifetimes of the mixed halogen pure red perovskite films obtained in Example 1 and Comparative Example 1 were fitted with the formula: ƞ(τ) = A1exp(-t / τ1) + A2exp(-t / τ2) (in the formula, ƞ(τ) is the fluorescence intensity decay over time, t is the independent variable time, τ1 and τ2 are the fluorescence lifetimes of the two processes of rapid decay (usually corresponding to non-radiative recombination) and slow decay (usually corresponding to radiative recombination), and A1 and A2 are the fluorescence intensity amplitudes of the two processes of rapid decay and slow decay at the moment of excitation, respectively). The specific fitting results are shown in Table 1. Among them, the average fluorescence lifetime τ of the mixed halogen pure red perovskite films obtained in Example 1 and Comparative Example 1 is shown in Table 1. avg The fitting formula is τ avg = (A1τ1 2 + A1τ1 2 ) / (A1τ1+ A1τ1).

[0035] Table 1. TRPL curve fitting results of the mixed halogen pure red perovskite films obtained in Example 1 and Comparative Example 1 Sample [A1] [tau1 (ns)] [A2] [tau]2 (ns) avg (ns)]]> ​ Comparative Example 1 0.66 1.07 0.34 3.98 2.98 Example 1 0.68 3.01 0.32 25.29 20.80 according to Figure 5 The PLQY curves in (a) and the average lifetime data in Table 1 can be used to calculate the radiative recombination rates (Ki) of the mixed halogen pure red perovskite films obtained in Example 1 and Comparative Example 1. r ) Nonradiative recombination rate (K) nr The specific results are shown in Table 2.

[0036] Table 2. Radiative and non-radiative recombination rates of the mixed halogen pure red perovskite thin films obtained in Example 1 and Comparative Example 1. Sample K r (s -1 )]]> K nr (s -1 )]]> K r / K nr ]]> Comparative Example 1 3.52 x 10 7 ]]> 3.00 x 10 8 ]]> 0.12 Example 1 3.90 x 10 7 ]]> 9.04 x 10 6 ]]> 29.96 The results in Tables 1 and 2 show that the average carrier lifetime of the mixed halogen pure red perovskite film, after modification with zinc acetate, increased from 2.98 ns to 20.80 ns, an increase of approximately 7 times; the nonradiative recombination rate (K0) also increased. nr From 3.00×10 8 s -1 Reduced to 9.04×10 6 s -1 This reduces the rate by two orders of magnitude; the ratio of the radiative recombination rate to the non-radiative recombination rate (K... r / K nr The value increased from 0.12 to 29.96, indicating that zinc acetate effectively passivated defects, suppressed the rapid decay process (τ1), and enhanced the slow radiative recombination process (τ2), thereby significantly improving the luminescence efficiency and fluorescence lifetime of the thin film.

[0037] Figure 6 The images show the morphology of the perovskite films obtained in Example 1 and Comparative Example 1, where (a) and (c) are scanning electron microscope (SEM) images of the perovskite films obtained in Comparative Example 1 and Example 1, respectively; (b) and (d) are atomic force microscope (AFM) height images of the perovskite films obtained in Comparative Example 1 and Example 1, respectively. Figure 6 As can be seen from (b) and (d) in the figure, the surface of the original perovskite film (the perovskite film without zinc acetate modification in Comparative Example 1) is rough and non-uniform, and its root mean square roughness (R) is high. q The perovskite film surface modified with zinc acetate in Example 1 became very smooth, with a root mean square roughness (Rm) as high as 3.88 nm. q The nanometer value was reduced to 1.71 nm, and the surface uniformity was significantly improved. (Scanning electron microscope image) Figure 6 (a) and (c) further reveal the evolution of grain size and distribution: the original perovskite film surface has a large number of irregularly shaped grains with a wide distribution range and obvious gaps between grains, so the surface coverage of the perovskite film is low; in contrast, the perovskite film modified with zinc acetate has a uniform grain distribution, no pinhole defects, and presents a dense and flat morphology.

[0038] Figure 7 This is a schematic diagram illustrating the mechanism by which zinc acetate-modified perovskite achieves defect passivation and halogen anchoring in this invention.

[0039] In summary, the improved performance of the zinc acetate-modified perovskite thin film and its light-emitting diode in this invention is mainly attributed to the Zn content in the zinc acetate. 2+ Ions and CH3COO - Ions simultaneously passivate defects in perovskite films, reduce deep-level defects, and improve radiative recombination efficiency. Unmodified perovskites contain two main types of defects: halide anion (bromine / iodide) vacancies that promote ion migration; and unsaturated lead ion sites located at grain boundaries and surfaces, which can become deep-level non-radiative recombination centers. These two types of defects severely reduce the luminous efficiency, color purity, and operational stability of perovskite materials. Figure 7It can be seen that, after the introduction of zinc acetate, zinc ions can act as Lewis acids, fixing halide ions through coordination bonds, thereby inhibiting ion migration and the generation of halide vacancies. Simultaneously, acetate ions, as Lewis bases, can coordinate with coordinatingly unsaturated lead ions, eliminating deep-level trap states. Test results showing improved photoluminescence quantum yield and extended carrier lifetime confirm that this dual-site synergistic passivation effect can comprehensively repair the above two types of defects, suppress non-radiative recombination processes, and effectively improve luminescence efficiency. Ultimately, the performance and spectral stability of the 683nm deep-red perovskite light-emitting diode device fabricated based on this material are significantly improved.

[0040] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described in this invention to avoid redundancy. Although preferred embodiments of this invention have been described, those skilled in the art, once they understand the inventive concept of this invention, can make other changes and modifications to these embodiments, and all such changes and modifications fall within the scope of this invention.

[0041] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. If such modifications and variations fall within the scope of equivalents of this invention, then this invention is also intended to include such modifications and variations.

Claims

1. A method for preparing a mixed halogen pure red perovskite light-emitting diode, characterized in that, Includes the following steps: CsI, PbI2, PbBr2 and Zn(CH3COO)2 were dissolved in a solvent in a molar ratio of 1.5:0.8:0.2:x to obtain a zinc acetate modified perovskite precursor solution. A zinc acetate-modified perovskite precursor solution was deposited on an anode substrate with an electron transport layer and an interface modification layer under an inert atmosphere, and then annealed to obtain a zinc acetate-modified perovskite light-emitting layer film. A hole transport layer, a hole injection layer, and a cathode layer were sequentially deposited on a zinc acetate-modified perovskite light-emitting layer film to obtain a mixed halogen pure red perovskite light-emitting diode. Among them, 0.1 <x<2。 2. The method for preparing a mixed halogen pure red perovskite light-emitting diode according to claim 1, characterized in that, The deposition method is spin coating, and the spin coating speed is 3000rpm~6000rpm, and the spin coating time is 30s~60s.

3. The method for preparing a mixed halogen pure red perovskite light-emitting diode according to claim 1, characterized in that, The annealing temperature is 80℃~120℃, and the annealing time is 10 minutes. 30 minutes.

4. A mixed halogen pure red perovskite light-emitting diode, characterized in that, The mixed halogen pure red perovskite light-emitting diode is prepared by the preparation method described in any one of claims 1 to 3, comprising an anode substrate and an electron transport layer, an interface modification layer, a zinc acetate modified perovskite light-emitting layer, a hole transport layer, a hole injection layer and a cathode layer sequentially prepared on the anode substrate.

5. The mixed halogen pure red perovskite light-emitting diode according to claim 4, characterized in that, The anode substrate is made of indium tin oxide and has a thickness of 120nm~150nm.

6. The mixed halogen pure red perovskite light-emitting diode according to claim 4, characterized in that, The cathode layer is made of Ag and has a thickness of 60 nm to 80 nm.

7. The mixed halogen pure red perovskite light-emitting diode according to claim 4, characterized in that, The electron transport layer is made of ZnO and has a thickness of 20nm~50nm.

8. The mixed halogen pure red perovskite light-emitting diode according to claim 5, characterized in that, The interface modification layer is made of polyethoxyethyleneimine and has a thickness of 5 nm to 15 nm.

9. The mixed halogen pure red perovskite light-emitting diode according to claim 5, characterized in that, The thickness of the zinc acetate-modified perovskite luminescent layer is 30 nm to 50 nm.

10. The mixed halogen pure red perovskite light-emitting diode according to claim 5, characterized in that, The hole transport layer is made of poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine) with a thickness of 20 nm to 50 nm; the hole injection layer is made of MoO3 with a thickness of 2 nm to 5 nm.